How Attitudes, Perceptions, Culture, and Gender Influence the Incidence of Chronic Kidney Disease? A Mixed-Method Study in Surakarta, Indonesia - Diyono, Diyono; Hartono, Hartono; Anantanyu, Sapja; Lestari, Anik (Journal of Ecohumanism, 2024)
Background: The prevalence of CKD has been rising in tandem with high rates of hypertension in Indonesia. Surakarta, a city in Indonesia, has notably high rates of both hypertension and CKD. Objectives: To analyze the factors influencing the increase in CKD cases in Surakarta City. Method: A mixed-method approach using a sequential explanatory design. The quantitative phase involved assessing the knowledge, attitudes, and preventive behaviors related to CKD among hypertensive patients. This was followed by a qualitative phase to investigate the experiences of patients diagnosed with CKD who had a history of hypertension. The study was conducted from February to June 2024. Results: (1) The average number of new CKD cases in 2023 was 33. (2) A positive correlation was found between knowledge and attitudes towards CKD prevention (p: 0.001; r: 0.963). Qualitative findings revealed the following factors influencing CKD incidence: (1) Inadequate knowledge and attitudes of patients regarding hypertension. (2) Misconceptions about antihypertensive medications. (3) Lack of family support due to gender and cultural factors. Conclusions: Knowledge, attitudes, perceptions, gender, and cultural factors significantly influence the increase in CKD cases among hypertensive patients in Surakarta City.